CD147/Basigin Limits Lupus Nephritis and Th17 Cell Differentiation in Mice by Inhibiting the Interleukin‐6/STAT‐3 Pathway. Issue 8 (28th July 2015) - Maeda, Kayaho; Kosugi, Tomoki; Sato, Waichi; Kojima, Hiroshi; Sato, Yuka; Kamimura, Daisuke; Kato, Noritoshi; Tsuboi, Naotake; Yuzawa, Yukio; Matsuo, Seiichi; Murakami, Masaaki; Maruyama, Shoichi; et al.
<x xml:space="preserve">Abstract</x> Objective Interleukin‐17 (IL‐17)–producing T cells (Th17 cells) play critical roles in the pathogenesis of immune‐related diseases, including systemic lupus erythematosus. However, the fundamental mechanism regulating Th17 cell differentiation is not fully understood. Recently, we demonstrated that plasma levels of CD147/basigin (Bsg) in patients with lupus nephritis (LN) were closely associated with disease activity. but the molecular mechanism involving Bsg has been elusive. Here, we addressed the role of Bsg in the pathogenesis of LN. Methods Injections of pristane (2, 6, 10, 14‐tetramethylpentadecane [TMPD]) were administered to Bsg−/− or Bsg+/+ mice to induce LN. The mice were killed 6 months after being injected, for histologic and biochemical analyses of the kidneys and spleens. Results Pristane induced LN more strikingly in Bsg−/− mice than in Bsg+/+ mice, even though humoral autoimmunity was similarly increased in both genotypes. The increased number of Th17, but not Th1, Treg cells, was augmented in Bsg−/− mice. The expression of IL‐17 was also increased in the kidneys of Bsg−/− mice, in proportion to LN disease activity. Furthermore, treatment with anti–IL‐17 antibody reduced LN disease activity in Bsg−/− mice. Complementary to these phenotypes of Bsg−/− mice, Bsg expression was enhanced in activated CD4+ T cells in vivo and in vitro. Bsg deficiency selectively augmented in vitro differentiation of naive CD4+ T cells to Th17 cells and STAT‐3 phosphorylation during this differentiation. Moreover, STAT‐3 phosphorylation was suppressed by crosslinking of Bsg with its antibody. Conclusion Bsg plays an indispensable role in Th17 cell differentiation as a negative regulator by suppressing the IL‐6/STAT‐3 pathway.